The Architecture of Batak Toba: An Expression of Living Harmoniously - Hanan, Himasari; Wonorahardjo, Surjamanto (Nakhara : Journal of Environmental Design and Planning, 2012)
Batak Toba people have a fi gurative imagination through which they orientate themselves to nature and the surrounding landscape. The architecture of the house is created to create a beautiful fi gure in the natural landscape as well as to act in moderating warm-humid climate. Dramatic roof forms have been developed as an expression of this culturally determined sensitivity towards natural forces and practical wisdom towards thermal comfort. Building a house deals with human needs within a structure of static and living components from the environment. Aesthetic qualities emerge genuinely out of the adaptive process within the corresponding multidimensional aspects of a living environment.